Longitudinal effects of interoceptive awareness training through mindful awareness in body-oriented therapy (MABT) as an adjunct to women's substance use disorder treatment: A randomized controlled trial. (1st May 2019) - Price, Cynthia J.; Thompson, Elaine Adams; Crowell, Sheila; Pike, Kenneth
Highlights: Significant longitudinal improvement in substance use. Significant longitudinal improvement in RSA, craving, and interoceptive awareness skills. Intervention dose effects on symptoms of depression and emotion dysregulation. Use of Mindful Awareness in Body-oriented skills reported through 12 months. Abstract: Background: Training in interoceptive awareness is a promising behavioral approach for improving substance use disorder (SUD) treatment. This study examined the longitudinal effects of Mindful Awareness in Body-oriented Therapy (MABT) as an adjunct to women's SUD treatment. MABT teaches interoceptive awareness skills to promote self-care and emotion regulation. Methods: Women in intensive outpatient treatment for SUD at three community clinics were recruited and randomly assigned to one of three study conditions Treatment as Usual (TAU) + MABT, TAU + Women's Health Education (WHE), and TAU only. Four assessments were delivered over one year (N = 187) baseline, 3, 6 and 12 months to examine primary outcome of percent days abstinent from substance use, and secondary outcomes of emotion dysregulation, craving, psychological distress, mindfulness and interoceptive awareness. Changes in outcomes across time were assessed using multilevel mixed effects linear regression. Results: Substance use improved significantly for MABT vs. TAU at 6 months and 12 months. Positive longitudinal effects on secondary outcomes for MABT were evident on respiratory sinus arrhythmia (RSA), a physiological index of emotion regulation; on craving; and on interoceptive awareness skills. Analyses based on participants who completed >75% of the intervention sessions revealed additional immediate significant improvements for MABT vs. TAU and WHE on depressive symptoms and emotion regulation difficulties and longitudinal improvement on mindfulness skills. Conclusions: Results show MABT to be efficacious for longitudinal health outcomes to support women's recovery as an adjunct to community-based SUD treatment.